Comparing Learning Motivation and Student Achievement Using Various Learning Models - Pamungkas, Danny Koerniawan (Unversitas Negeri Malang, 2018)
This study aims to examine the differences in student learning and learning outcomes between different learning models between using collaborative learning models Contextual Teaching and Learning and Hypnoteaching with Learning Contextual Teaching and Role Playing. The research subjects used were class X students of Accounting Department at SMK PGRI Rogojampi who won 64 people. The type of research used is quasi-experimental research, using research instruments about pre-test and post-test and questionnaire. The findings showed showed that there are significant differences in student achievement and learning motivation between collaborative learning models Contextual Teaching and Learning and Hypnoteaching with Contextual Teaching and Role Playing.